2017
DOI: 10.1186/s12911-017-0511-8
|View full text |Cite
|
Sign up to set email alerts
|

German dentists’ websites on periodontitis have low quality of information

Abstract: BackgroundThe internet is an increasingly relevant source of health information. We aimed to assess the quality of German dentists’ websites on periodontitis, hypothesizing that it was significantly associated with a number of practice-specific parameters.MethodsWe searched four electronic search engines and included pages which were freely accessible, posted by a dental practice in Germany, and mentioned periodontal disease/therapy. Websites were assessed for (1) technical and functional aspects, (2) generic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…In another study, Schwendicke et al. (2017) assessed the quality of German dentists’ web sites on periodontitis using Minervation validation instrument for healthcare web sites (the LIDA instrument) and DISCERN toolkit. It was found that most of the German dentists’ web sites on periodontitis were not fully trustworthy and in need of improving the quality of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Schwendicke et al. (2017) assessed the quality of German dentists’ web sites on periodontitis using Minervation validation instrument for healthcare web sites (the LIDA instrument) and DISCERN toolkit. It was found that most of the German dentists’ web sites on periodontitis were not fully trustworthy and in need of improving the quality of information.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, it has become quite common for many individuals to make a search on the Internet for a dental health professional when choosing a clinic or a dentist. The information provided on dentists’ web sites may reflect the chairside information given by those dentists, and this also comprises the etiology, prevention, therapy, and maintenance of periodontitis (Schwendicke, Stange, Stange, & Graetz, 2017). However, poor quality online information can confuse patients and may be responsible for mistrust to dental professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Bearing in mind that 25% of the population in The Netherlands has inadequate health literacy, the potential implications of the readability results on processing online health information might be even more severe [23]. Hypothetically, high website quality might be expected by centrally located practices or the ones financially managed by multiple owners [14]. Websites of practices located in multiple provinces were assigned significantly higher BDC scores than the rest, indicating superior website optimization.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the widespread acceptance of orthodontics by the general Dutch population and shortage of practicing orthodontists, especially in non-metropolitan areas, 27-40% of the orthodontic caseload is being served by dentists [12,13]. Given practice-specific parameters like location (i.e., urban vs. rural areas), ownership status (i.e., multi-owner vs. single-owner practice), and professional title (i.e., dentists vs. orthodontists) may have a certain impact on the website's quality [14], it would be interesting to investigate the informational content of the websites of the practices of orthodontic treatment providers in The Netherlands. Thus, the aims of this study were to examine the compliance of Dutch orthodontic practices to EU regulations (CED), readability of the posted orthodontic information, website design, and possible relationship of the aforementioned website features with practice location and professional qualification of practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Another previous study revealed that 87% of UK dentists reported having changed their practice as a result of reading a research article [34]. Further, it has been pointed out that most German dentists' websites are not fully accurate with regard to periodontitis [35] and that the problem with textbooks as a source of evidence is that the information may be substantially out of date at the time of publication [36]. Taken together, the results of this study suggest that frequent use of evidence-based information in Englishlanguage scientific articles may help improve Japanese dentists' decision making about IPC.…”
Section: Discussionmentioning
confidence: 99%